Pesan-Pesan Dakwah dalam Film 99 Nama Cinta - Nuraeni Putri; Malki Ahmad Nasir (UNISBA Press, 2022)
In carrying out da'wah, the media is needed for da'wah messages to be conveyed, one of the media that is very easy to influence the community, namely film media, because many people like to watch the movies, besides that the film always provides us the current various entertains so that the messages contain in the movies are very relevant to everyday life. Therefore, the researcher will analyze the da'wah that messages contain in the film 99 Names of love using semiotic analysis of Roland Barthes which is on denotative meaning. The purpose of this study is to find out what the messages of aqidah, sharia, muamalah, and akhlaq that are contained in the film 99 Names of Love. The benefits of this research are expected to provide the both in terms of academic and practical thing. The method used in this study is a qualitative descriptive approach, the technique of data collection, the triangulation of data and documentation, where the researcher will transcribe the dialogues in each scene and analyze them, also use other relevant books and other media. In the results of the research, there are ten da'wah messages are found in the film 99 Names Of Love. There are four messages of aqidah including faith in Allah's destiny, the gratitude to Allah, Allah's destiny on death, Allah is the protective of whole creations, two messages on sharia including that are always keeping the wudhu and being shalawat to the Prophet, while one message on muamalah is being friendships, finaly three messages on akhlaq are how to be kind, helping, and apologizing.